Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jchemed.6b00093
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Explanations in the Laboratory To Connect Theory and Practice: The Decision/Explanation/Observation/Inference Writing Method

Abstract: While many faculty seek to use studentcentered, inquiry-based approaches in teaching laboratories, transitioning from traditional to inquiry instruction can be logistically challenging. This paper outlines use of a laboratory notebook and report writing-to-learn method that emphasizes student self-explanations of procedures and outcomes, specifically the Decision/Explanation/Observation/Inference (DEOI) method. The DEOI method fosters a studentcentered learning environment but can be used with traditional expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
(38 reference statements)
0
15
0
3
Order By: Relevance
“…Links between the experiment and scientific ideas are not always explicit, neither in instruction nor in students actions (Abrahams & Reiss, 2012). Without scaffolding, students may struggle to establish these links, thus, just doing appears meaningless for the students (Abrahams & Reiss, 2012;Schwichow, Zimmerman, Croker, & Härtig, 2016;Van Duzor, 2016) and may be neither appealing nor effective for their learning. Indeed, the contribution of laboratory work to students' conceptual understanding (Abrahams & Reiss, 2012) as well as to students' interest (Holstermann, Grube, & B€ ogeholz, 2010) has been questioned, making the weak correlation between interest in laboratory work and conceptual understanding less surprising.…”
Section: Interplay Between Interest In School Science Activities Anmentioning
confidence: 99%
“…Links between the experiment and scientific ideas are not always explicit, neither in instruction nor in students actions (Abrahams & Reiss, 2012). Without scaffolding, students may struggle to establish these links, thus, just doing appears meaningless for the students (Abrahams & Reiss, 2012;Schwichow, Zimmerman, Croker, & Härtig, 2016;Van Duzor, 2016) and may be neither appealing nor effective for their learning. Indeed, the contribution of laboratory work to students' conceptual understanding (Abrahams & Reiss, 2012) as well as to students' interest (Holstermann, Grube, & B€ ogeholz, 2010) has been questioned, making the weak correlation between interest in laboratory work and conceptual understanding less surprising.…”
Section: Interplay Between Interest In School Science Activities Anmentioning
confidence: 99%
“…In addition, through the report writing, students could build arguments that were positively correlated to the oral communication ability (Walker & Sampson, 2013). Duzor (2016) reported that report writing could connect the theories and practices in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to constructing arguments, composing inquiry reports can hone critical thinking skills (Contakes, 2016;Walker & Sampson, 2013;Quitadamo & Kurtz, 2007). The ability to discuss inquiry in reports can relate theories studied in the classroom to laboratory investigation results (Duzor, 2016).…”
Section: Figure 4 Effect Of Od3r Methods For Scientific Attitudesmentioning
confidence: 99%